Multiletramentos nas aulas de língua inglesa no ensino fundamental: experiência de mediação por vlogs - Morais, Daniela Miguel de Souza (2021)
Working with Multiliteracies is justified by the very evolution of society and the various changes that have occurred in the social, political, economic and educational spheres. Those changes led to the emergence of the so-called Information and Communication Digital Technologies (ICDT). This research had as main objective to investigate experiences of multiliteracies, mediated by the production of vlogs for linguistic exchange in English Classes. The research was carried out in a municipal school, in the rural area of São José de Piranhas, Alto Sertão of Paraíba. It is a qualitative research, with an ethnographic nature, with characteristics that also define it as action research. What guided this work was the following question: "how digital experiences in middle school, mediated by the production of videos, can contribute to linguistic exchange in English?" Based on that, we divided our research into five stages. The first one consisted of the selection and registration of the works that make up the theoretical framework of the dissertation. The second stage took place from the contact we made with the institution where the research was conducted, through a meeting with the principal and the parents and / or legal guardians of the research collaborators. In the third stage, there was the elaboration and application of a questionnaire in order to acquire necessary information for the development of the research, such as the initial motivation for learning English as an additional language and the contact that the participants establish with English outside the school. The fourth stage consisted of the application of a Didactic Sequence covering the genre vlog. And, finally, in the fifth stage, we applied a second questionnaire to find out the opinion of the participants in relation to the activities developed and the possible consequences for English language learning of. Our work had as theoretical basis the Pedagogy of Multiliteracies (ROJO, 2012), the Complexity that is present in the process of teaching and learning additional languages (PAIVA, 2011), and the Sociocultural Perspective of knowledge construction (VYGOTSKY, 2001 and FIGUEIREDO, 2019). After all this, we realized that working with multiliteracies and ICDT in English language classes, when based on proper planning, can bring contributions to the motivation, identity and autonomy of the learners, elements that determine the complex teaching and learning process of English.